Investigations of dark, bright, combined dark-bright optical and other soliton solutions in the complex cubic nonlinear Schrodinger equation with ?-potential - Baskonus, Haci Mehmet; Sulaiman, Tukur Abdulkadir; Bulut, Hasan; Akturk, Tolga (Academic Press Ltd- Elsevier Science Ltd, 2018)
In this study, using the extended sinh-Gordon equation expansion method, we construct the dark, bright, combined dark-bright optical, singular, combined singular solitons and singular periodic waves solutions to the complex cubic nonlinear Schrodinger equation with delta-potential. The conditions for the existence of the obtained solutions are given. To present the physical feature of the acquired result, the 2D and 3D graphs are plotted under the choice of suitable values of the parameters. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: The extended ShGEEM; NLSE; delta-potential; Optical soliton